Retoryka populistyczna w parlamentarnej kampanii wyborczej w dobie kryzysu migracyjnego - Adamczewska, Kinga (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
The main purpose of the study was to examine whether populist rhetoric was present in the statements of the leaders of five political parties (PO, PiS, PSL, Kukiz'15, KORWiN), during the parliamentary election campaign in 2015 in Poland. Analysis of political statements in the traditional media and online media in the period 11—23 October 2015 allowed positively verify the research hypothesis. Leaders of Polish political parties have used populist rhetoric — usually using the negative image of refugees, presenting them as a threat to the state and citizens.